Factor analysis: Competency framework for measuring student achievements of architectural engineering education in Indonesia - Rihab Wit Daryono; V. Lilik Hariyanto; Husaini Usman; Sutarto Sutarto (REID (Research and Evaluation in Education), 2020)
This study aims to prove the validity test and estimate the instrument's reliability to measure student achievement in the department of architectural engineering education in Indonesia. The cluster random sampling technique was used to determine the number of students consisting of 103 vocational education students. This study uses a survey method to examine and analyze the structure of students' competency achievements factors. The collected empirical data were analyzed using descriptive and inferential statistics using Exploratory Factor Analysis (EFA). EFA test is intended to reveal factors that can be formed from instruments that have been established for measurement of achievements of vocational student competencies. The analysis results using EFA showed that the instrument had good construct validity. The result of this research shows that the instrument test for measuring the achievement of student competencies has good reliability and consists of 30 competency items covering ten competency aspects, namely general competencies, technical drawing, statically structures, basic building construction, land measurement engineering, software application and building interior design, road and bridge construction, estimated construction costs, building construction and utility, creative and entrepreneurship product competencies.